Notes on Indian wolf spiders: III. Genera Acantholycosa Dahl, 1908, Evippomma Roewer, 1959, Hippasosa Roewer, 1960 and Trochosa C.L. Koch, 1847 (Araneae: Lycosidae) - Sankaran, Pradeep M.; Caleb, John T.d. (Zootaxa, 2023)
The species of the genera Acantholycosa Dahl, 1908, Evippomma Roewer, 1959, Hippasosa Roewer, 1960 and Trochosa C.L. Koch, 1847 described/recorded from India, are reviewed. The following new combinations are recognized: Arctosa dhikala comb. et nom. nov. (ex. Trochosa), Arctosa kalpiensis (Gajbe, 2004) comb. nov. (ex. Hippasosa), Evippa baltoroi (Caporiacco, 1935) comb. nov. (ex. Acantholycosa), Pardosa evippiformis Caporiacco, 1935 comb. rest. (ex. Evippomma), and Pirata punctipes (Gravely, 1924) comb. nov. (ex. Trochosa). Photographs of all the examined type material and supplementary descriptions for A. dhikala comb. et nom. nov., E. baltoroi comb. nov., P. evippiformis comb. rest., and P. punctipes comb. nov. are provided. Lectotypes have been designated for E. baltoroi comb. nov., P. evippiformis comb. rest. and P. punctipes comb. nov. With the new combination for T. punctipes, the genus Pirata Sundevall, 1833 is recorded for the first time in India, and that for A. baltoroi and E. evippiforme show the record of the genera Acantholycosa and Evippomma from India is incorrect.